Análise de minerais por Ativação Neutrônica Instrumental (INAA) e Espectrometria de Massa (ICP-MS) em cultivo de camarões marinhos (L. vannamei) em bioflocos - Leonardo Vaz Pereira (2019)
According to the National Research Council (NRC) some microminerals (Cu, Zn, Mn and Se) are considered required for development of Litopenaeus vannamei. However, little is known about the fate of these elements in aquaculture systems that employ low or no water exchange such as the Biofloc Technology system (BFT). The objective of this study was to analyze the concentration of microminerals required and toxics present in feed, biofloc and in shrimp raised in superintensive system (400 shrimps/m2), distant from the coast with no water renewal in low salinity. In the first stage of the research (chapter 2), a multielementary analysis of aquacultural inputs used in shrimp farming was performed using the Instrumental Neutron Activation Analysis (INAA), based on the k0 method using nuclear reactor as referencial technique. Same samples were also analyzed by Inductively Coupled Plasma Mass Spectrometry (ICP-MS) with focus for all minerals cited as essencial. We observed a greater accumulation of elements in the shrimp cephalothorax when compared with the rest of the body. Trophic transfer factor (TTF) was > 1 for essentials Cu and Se, via feed for whole animal samples. In relation to commercial feed, the biofloc concentrated all the required elements. In the second phase (chapter 3), was observed a greater accumulation of several elements, classified as potentially toxic to production system were identified. Concentrations of lanthanides and actinides elements in biofloc were also observed, elements such as bromine (Br) and cesium (Cs) obtained TTF of the aquafeed used for the animal > 1. Of the 28 elements present in the inputs, 23 were concentrated in the production system via suspended solids and 16 elements were incorporated into the animal tissue composition. Both supplies and animals were within the limits required by Brazilian legislation. Special attention should be given to research into closed aquaculture systems, as there are a variety of elements that can accumulate along the production cycles and their effects on heath and nutrition of cultured animals and human beings are little known